The Extent of Social Contribution of Venture Capital Organisations to Funded Financed Companies - Dziri , Houda; Jarboui , Anis (Asian Journal of Empirical Research, 2019)
The major objective lying behind the conduction of the present work lies in investigating the social advantages likely to be brought about by the venture capitalist to the funded firm. More specially, it treats the venturer’s financial contribution as based on a number of human resources management related practices. Overall, the reached results, relevant to a sample involving 150 companies proved to indicate that the financial participation of this mode of financial intermediation turns out to be partially associated with a social contribution. In effect, it has been discovered that a number of the advanced practices, suggested as social contribution relating measures, do not prove to stand as part of the changes targeted by the venture capitalist to take place in a bid to enhance the firm’s social performance, nor were they intended to further improve the added values already achieved. Actually, such a strategy could well reflect some special features characterize the Tunisian venture capital mode of financing.